Protective Effects of Deferoxamine on Vestibulotoxicity in Gentamicin-Induced Bilateral Vestibulopathy Rat Model - Kim, Hyo-Jung; Lee, Jin-Ok; Kim, Ji-Soo (Frontiers in Neurology, 2021)
Introduction. Administration of aminoglycoside antibiotics (AG) is one of the most common cause of ototoxicity. This study aimed to determine the protective effects of deferoxamine, an iron-chelating agent, on vestibulotoxicity using an intratympanic gentamicin injection (ITGM)-induced bilateral vestibulopathy rat model. Methods. Fifteen Sprague-Dawley rats were randomly assigned to either the ITGM only (n=5), the ITGM combined with intramuscular deferoxamine (DFO) injection (ITGM+DFO, n=5), or the intratympanic normal saline (control, n=5) group. The rats in the ITGM+DFO group received intramuscular injection of 150 mg/kg deferoxamine 30, 90, and 150 minutes after the ITGM injections. The vestibular function was evaluated using the rotarod and open field test every 3 days after the injection until the day 16 when the rats were subjected to histologic changes. Results. The rats in the ITGM only group began to show significantly impaired vestibular function two days after ITGM into both ears. In contrast, the vestibular function was maintained in the control and ITGM+DFO groups without a difference throughout the experiments. The rats in the ITGM only group showed a near complete loss of the type I and II hair cells and a collapse of the sensory epithelium both in the saccule and utricle. In contrast, the rats in the ITGM+DFO and control groups showed a relatively well-preserved sensory epithelium including the hair cells, cilia, and otolith layer. Conclusion. This study provides experimental evidence for preventive effects of iron-chelating agents on AG-induced vestibulotoxicity. Simultaneous administration of iron-chelating agents may be considered when using ototoxic agents, especially in those considered to be vulnerable to toxic damage of the inner ear.